A combination mathematical model (FA, AHP, FARAS) for ranking the effective factors on strategic outsourcing in supply chain of small and medium manufacturing enterprises. (2016) - Nikabadi, Mohsen Shafiei; Zamani, Leila
Outsourcing is one of the most popular business strategy in the global era. Outsourcing can bring tremendous benefits to organisations, but if an outsourcing decision is not precise and factors influencing the outsourcing decision are not considered, it can also bring irreparable damage. This study is to identify and rank the factors affecting the outsourcing on the basis of strategic perspective in supply chains of small and medium manufacturing enterprises. In this study, the factors influencing the strategic outsourcing decisions were determined on the basis of prior literature. In this approach, the refinement of the parameters using factor analysis was conducted to determine the most important sub-indices, and then due to the multidimensional nature of these factors, the analytic hierarchy process technique used for the weighting of factors and fuzzy additive ratio assessment method are used for ranking sub-criteria factors influencing strategic outsourcing. The findings show that the 'quality' is the most important factor and 'management agent' is the factor with the lowest importance.